Instant Autodesk Revit 2013 customization with .NET how-to : a supercharged guide to creating your own plugins, add-ons, and customizations for Revit with .NET /: a supercharged guide to creating your own plugins, add-ons, and customizations for Revit with .NET. (2013) - Unknown
No abstract available